An empirical study on flow experience regulation in reducing English listening anxiety among high school students - Liu, Xiu; Lin, Mingjin (Frontiers in Education, 2025)
This study investigates the moderating effect of flow experience on English listening anxiety in the context of high school English instruction in China. A total of 105 first-year high school students participated in the experiment. Quantitative data collected through tests and questionnaires revealed that flow experience significantly reduced listening anxiety by enhancing learners' concentration, task engagement, and intrinsic motivation. Moreover, flow, as a positive psychological state, was associated with improved listening comprehension. Among students with higher levels of anxiety, flow played a crucial regulatory role by buffering the negative effects of anxiety through cognitive, emotional, and behavioral mechanisms. These findings suggest that incorporating flow-based strategies into listening instruction may serve as an effective approach to reducing anxiety and improving learning outcomes.